2008
DOI: 10.1017/s1751731107001024
|View full text |Cite
|
Sign up to set email alerts
|

Developmental orthopaedic disease in limbs of foals: between-breed variations in the prevalence, location and severity at weaning

Abstract: Developmental orthopaedic disease (DOD) affects all breeds and is a common cause of pain and lameness for horses in sports. A thorough knowledge of between-breed variations for the prevalence of DOD, for its distribution among the various joints and for its severity at earlier stages in the disease process is needed in order to improve the relevance and the cost-effectiveness of DOD screening protocols. However, no prevalence study for DOD simultaneously performed on several breeds with similar farming systems… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 21 publications
1
9
0
Order By: Relevance
“…There are contradictory findings in the literature regarding the effect of gender. The incidence of the disease is 2 times higher in males and several other studies have reported a higher prevalence tendency in males (5,10). In this study, it was determined that gender was not a significant difference in the appearance of the disease, although it was a slight bias towards males.…”
Section: Discussionmentioning
confidence: 50%
See 1 more Smart Citation
“…There are contradictory findings in the literature regarding the effect of gender. The incidence of the disease is 2 times higher in males and several other studies have reported a higher prevalence tendency in males (5,10). In this study, it was determined that gender was not a significant difference in the appearance of the disease, although it was a slight bias towards males.…”
Section: Discussionmentioning
confidence: 50%
“…The etiopathogenesis of DOD has been debated in the literature by different researchers for years (4,5). The cause of DOD in foals is unknown, but putative factors include nutritional excesses or imbalances, genetics, growth rate, hormonal disorders, trauma and biomechanical forces, metabolic dysfunctions (6,7).…”
Section: Introductionmentioning
confidence: 99%
“…The majority of these developmental abnormalities at the distal intermediate ridge of the tibia occur on the craniodistal and lateral aspect and are most commonly diagnosed on either the LM or D45M‐PLO projection . Previous studies report the prevalence of radiographically apparent developmental orthopedic disease in 6‐month‐old horses to be 25% in Warmbloods, 41% Standardbreds, and 34% in Thoroughbreds . Because specific intra‐articular areas are commonly affected, radiographic images are often reviewed for abnormalities in a prescribed number of projections per joint.…”
Section: Discussionmentioning
confidence: 99%
“…15,16 Most descriptive studies have focused on the risk of musculoskeletal injury or fatality of Thoroughbreds during racing or training. 15,16 Most descriptive studies have focused on the risk of musculoskeletal injury or fatality of Thoroughbreds during racing or training.…”
Section: Risk Of Orthopedic Disease Injury or Fatality In Thoroughbmentioning
confidence: 99%
“…66 Changes in the metacarpo-(36%)/tarso-(44%) phalangeal joints were also commonly identified. 16 Warmblood and Thoroughbred foals were mainly affected at the dorsal aspect of the hind fetlock (36% and 18%, respectively), the fore fetlock (32% and 18%, respectively), the femoro-patellar joint (28% and 15%, respectively) and the carpus (25% and 15%, respectively). More specifically, the medial femoral condyle in the stifle was the commonly affected location with 188 (41%) horses showing either uni-or bi-lateral changes at this site.…”
Section: Osteochondrosismentioning
confidence: 99%